Feasibility of a UK community-based, eTherapy mental health service in Greater Manchester: repeated-measures and between-groups study of 'Living Life to the Full Interactive', 'Sleepio' and 'Breaking Free Online' at 'Self Help Services'. Issue 7 (20th July 2017) - Elison, Sarah; Ward, Jonathan; Williams, Chris; Espie, Colin; Davies, Glyn; Dugdale, Stephanie; Ragan, Kathryn; Chisnall, Leanne; Lidbetter, Nicky; Smith, Keith
Abstract : Objectives: There is increasing evidence to support the effectiveness of eTherapies for mental health, although limited data have been reported from community-based services. Therefore, this service evaluation reports on feasibility and outcomes from an eTherapy mental health service. Setting: 'Self Help Services', an Increasing Access to Psychological Therapies (IAPT) eTherapy service in Greater Manchester. Participants: 1068 service users referred to the service for secondary care for their mental health difficulties. Interventions: Participants were triaged into one of three eTherapy programmes: 'Living Life to the Full Interactive' for low mood, stress and anxiety; 'Sleepio' for insomnia; and 'Breaking Free Online' for substance misuse, depending on clinical need. Primary outcomes measures: Standardised psychometric assessments of depression, anxiety and social functioning, collected as part of the IAPT Minimum Data Set, were conducted at baseline and post-treatment. Results: Data indicated baseline differences, with the Breaking Free Online group having higher scores for depression and anxiety than the Living Life to the Full Interactive (depression CI 1.27 to 3.21, p<0.0001; anxiety CI 077 to 1.72, p<0.0001) and Sleepio (depression CI 1.19 to 4.52, p<0.0001; anxiety CI 2.16 to 5.23, p<0.0001) groups. Promising improvements in mental health scores were found within all three groups (all p<0.0001), as were significant reductions in numbers of service users reaching clinical threshold scores for mental health difficulties (p<0.0001). Number of days of engagement was not related to change from baseline for the Living Life to the Full or Sleepio programmes but was associated with degree of change for Breaking Free Online. Conclusion: Data presented provide evidence for feasibility of this eTherapy delivery model in supporting service users with a range of mental health difficulties and suggest that eTherapies may be a useful addition to treatment offering in community-based services.